PENGARUH PENDIDIKAN KEWIRAUSAHAAN DALAM MENUMBUHKAN MINAT BERWIRAUSAHA - Budi, Budi; Fensi, Fabianus (Jurnal Pengabdian dan Kewirausahaan, 2018)
Indonesia needs 5.8 million new entrepreneurs to achieve an ideal entrepreneurial ratio of 4% of the population. The need to create new entrepreneurs has led many educational institutions to include entrepreneurship education in their curriculum. Entrepreneurship education is a development activity for those who want to try or become entrepreneurs and activities to improve understanding and knowledge of entrepreneurship (Fitriati and Hermiati, 2010). The goal of entrepreneurship education is so that learners learn to understand entrepreneurship, learn to have if entrepreneurship, and learn to be entrepreneur (Heinonen and Poikkijoki, 2006). Entrepreneurship education remains in debate on the extent to which entrepreneurship education has an influence on learners, the accuracy and effectiveness of entrepreneurship teaching methods, and the debate on whether entrepreneurship can be taught. This study aims to analyze whether the entrepreneurship education conducted has an impact to arouse students' entrepreneurial intentions. Subjects in this study are students of Entrepreneurship class. Concept operationalization is done by adopting Mohamad et al (2015) research. Data analysis technique uses Different T-Test Differences. Result showed that there was no significant difference in the intention of entrepreneurship of learners. Therefore, a more thorough research on the effectiveness of entrepreneurship education in developing the entrepreneurship aspirations of learners, and the evaluation of teachers, curriculum and methods of implementation of entrepreneurship classes should be conducted.Keywords: entreprenuship, entreprenurship education, entreprenurial intention, effectiveness